Organisational Design for Co-Management : Comparing Four Committees in Nunavik - Peters, Evelyn (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2003)
The Brundtland Report focused on the importance of institutional arrangements in solving pressing resource problems. Co-management arrangements have been an important avenue for Aboriginals to participate in the management of country foods, and the environments that support them. The James Bay and Northern Quebec Agreement, signed in 1975, created several co-management bodies that focus on environments and wildlife. This paper draws on the extensive body of literature on co-management to develop three principles to evaluate these arrangements. These principles have to do with the ability of committees to adapt to changing environments and demands, their effectiveness in influencing government decision-making, and their ability to represent Aboriginal cultures and values. Each of the co-management bodies created by the Agreement is evaluated according to these criteria.